Sex differences in mechanisms, presentation and management of ischaemic heart disease. Issue 1 (July 2015) - Crea, Filippo; Battipaglia, Irma; Andreotti, Felicita
Abstract Ischaemic heart disease (IHD) is the leading cause of death in women as in men, although presentation in women is on average 7–10 years later. Recent temporal trends show declining IHD incidence and mortality among men but not among women. Other gender differences concern the prevalence of underlying mechanisms. Women more frequently than men have nonobstructive epicardial artery disease, nonatherosclerotic spontaneous coronary artery dissection, stress cardiomyopathy, plaque erosion, microvascular dysfunction, and a heavier risk factor burden, even after adjustment for age. Atypical symptoms of IHD are more common in women. The crude outcomes of both chronic and acute coronary syndromes are worse in women than in men, in relation to older age and comorbidities. After adjustments, in-hospital mortality after acute myocardial infarction is reported to remain higher among younger women compared to male peers. Such female vulnerability, in apparent contrast with the delayed average onset and lesser extent of epicardial atherosclerosis, likely reflects gender differences in early presentation, as well as in mechanisms, prevention, diagnosis, comorbidities, management, and response to treatment. Recognition and quality of care of IHD are still not the same for women and men.